Investigation of Bird Strike Damage on Fokker 100 Airplane Wing and Nose - Mirzaei, mojtaba (Journal of Mechanical Engineering and Technology (JMET), 2020)
Bird strike or the collision of birds to the flying airplane is one of the common threats which reduces the safety of flying vehicles. Numerical analysis is so important to predict the behavior of airplanes body and nose in birds strike and it plays an important role to reduce the project cost and prevent unexpected damages. In this paper, it is tried to study the influence of birds strike on Fokker 100 airplane using the finite element method. In order to verify the proposed method, an experimental bird strike on a plane is studied. Then birds strike on the airplane wing and nose are numerically studied to investigate the amount of damage due to this phenomenon.